Implementing of Government Technique on Community Empowerment Program through Paddy Field Tourism in Pematang Johar Village - Mujahiddin, Mujahiddin (Journal of Community Service and Society Empowerment, 2025)
Since its inauguration in early 2020, rice field tourism in Pematang Johar Village has had a positive impact on the village government and also the village community. Rice field tourism has an impact on community empowerment by opening up new jobs. Research data collected using a grounded research approach has succeeded in finding that the implementation of government techniques carried out by the Pematang Johar Village Government began with forming a welfare discourse containing promises of improving the economy for residents and also implementing various forms of regulations, both written and unwritten, to each subject involved in managing rice field tourism. The forms of unwritten regulations that were successfully identified were the discourse on welfare and economic income, advice, and reprimands. This regulation is considered effective in forming a compliant and disciplined body. Meanwhile, written regulations are only introductory regulations to produce procedural agreements.